The tomb robbers - King, SJ.; O'Shea, Ellie (New York, New York : DK Publishing, 2020)
"Someone is trying to steal the pharoah's treasure and only the Secret Explorers can stop them. Gustavo and Kiki are undercover in Ancient Egypt and on the case, but the bad guys won't give up easily . . . " -- Cover.
Keywords: Time travel -- Juvenile fiction; Pyramids -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Hieroglyphics -- Juvenile fiction; Egypt -- Juvenile fiction